KETERAMPILAN BERPIKIR TINGKAT TINGGI PADA EVALUASI PEMBELAJARAN TEMATIK YANG DIGUNAKAN GURU KELAS IV DI SD NEGERI 81 PALEMBANG - Laili Mutia Qodra; Asnimar Asnimar; Laihat Laihat (Jurnal Inovasi Sekolah Dasar, 2021)
This study aims to describe information about higher order thinking skills in the evaluation of thematic learning used by grade IV teacher at SD Negeri 81 Palembang. This research is a qualitative descriptive research. The subject and objects in this study were the grade IV teachers and the learning evaluation used by the grade IV teachers. Data were collected using research instruments through interviews and document. The result of this study indicate that the evaluation of learning in the daily assessment of theme 1 is 4% HOTS and 96% LOTS, the daily assessment of theme 2 is 24% HOTS and 76% LOTS, the daily assessment of theme 3 is 20% HOTS and 80% LOTS, theme daily assessments 4 there are 16% HOTS and 84% LOTS and the mid semester assessment is 7% HOTS and 93% LOTS. So the learning evaluation used by the teacher is only a small part using operational verb (KKO) which contains higher order thinking skills and are dominated by operational verb (KKO) which lead to lower order thinking skills. Keyword: Higher Order Thinking Skills, Evaluation, Thematic Learning, Teacher, Class IV.